Health in All Policies and intersectorality in Latin America and the Caribbean, 2011 - 2021: a scoping review - Fabio Alberto Escobar Díaz; Zuly Andrea Rodriguez Corredor (Revista de Salud Pública, 2023)
Introduction: Intersectoriality, since the Alma Ata Conference in 1978, has become a fundamental part of the political discourse on public health, social determinants, and health promotion to address health problems in society. Following the above, it is important to identify the research carried out in Latin America and the Caribbean on this topic in the last decade.